2015
DOI: 10.1016/j.humpath.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Invasion rather than nuclear features correlates with outcome in encapsulated follicular tumors: further evidence for the reclassification of the encapsulated papillary thyroid carcinoma follicular variant

Abstract: Summary The prognosis of the encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC) and its relationship to encapsulated follicular carcinoma (EFC) and follicular adenoma (FA) is subject to controversy. All EFVPTCs, EFCs, and FAs identified at a single institution between 1981 and 2003 were analyzed microscopically. A cohort of FAs from a different hospital was also examined. EFVPTCs were subdivided into noninvasive EFVPTC (NIEFVPTC) and invasive EFVPTC (IEFVPTC) displaying capsular/vascular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
110
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 31 publications
(34 reference statements)
6
110
0
1
Order By: Relevance
“…In this cohort and in identical noninvasive tumors reported in the literature, there was no evidence of metastatic disease (structural or biochemical). 12 Follow-up (mean 11.2 years) showed a complete lack of latent or unrecognized disease and no need for prophylactic central lymph node dissection for this tumor type.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this cohort and in identical noninvasive tumors reported in the literature, there was no evidence of metastatic disease (structural or biochemical). 12 Follow-up (mean 11.2 years) showed a complete lack of latent or unrecognized disease and no need for prophylactic central lymph node dissection for this tumor type.…”
Section: Discussionmentioning
confidence: 87%
“…35 Previous studies have concluded that adequate therapy for encapsulated follicular variant of papillary thyroid carcinoma should be a lobectomy [35][36][37] without radioactive iodine. 1,12,14,15,29 Radioactive iodine should be employed only when a clinical benefit can be reasonably expected which cannot be shown for this tumor type, and thus should be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors with either capsular penetration or lymphovascular invasion would be designated as an encapsulated FVPTC with invasion. Approximately one third of encapsulated FVPTC are invasive (7)(8)(9)11,15). Encapsulated FVPTCs with invasion metastasize in a manner similar to FTC with distant metastases as opposed to lymph node metastases (8,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of encapsulated FVPTC are invasive (7)(8)(9)11,15). Encapsulated FVPTCs with invasion metastasize in a manner similar to FTC with distant metastases as opposed to lymph node metastases (8,15,16). Although rare, these patients can die of their disease (8,15).…”
Section: Introductionmentioning
confidence: 99%